IMPLIKASI SOSIAL BUDAYA DAN ILMU PENGETAHUAN DAIAM PERKEMBANGAN BAHASA ARAB - Alawiyah, Azizah (Al Qalam, 2013)
As a tool of humans' communication, language is not static, but dynamic and progressive. The socio-cultural changes and the development of sciences give an impact toward the development of Arabic. The use of Arabic is not only limited for religious subjects, but also for daily communication and sciences. Many new vocabularies and academical terms absorbed into Arabic are derived from Romanic, Persian, Greek, Sanskrit, and other languages. Hence, it is clear to demonstrate that Arabic is a language of unifying people. Key Words: The Development of Language, The Socio-Cultural Changes, The Development of Sciences.